2018
DOI: 10.1007/s12253-018-0527-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Levels of VEGF-A, VEGF-C, VEGF-D, their Soluble Receptor - VEGFR-2 and Applicability of these Parameters as Tumor Markers in the Diagnostics of Breast Cancer

Abstract: VEGF family members are important factors in promoting angio- and lymphangiogenesis. The aim of this study was to investigate concentrations, diagnostic utility and power of VEGF-A, VEGF-C, VEGF-D and VEGFR-2 in comparison to CA15–3 in breast cancer (BC) patients. The study included 120 BC patients and 60 control patients (28 with benign breast tumors and 32 healthy women). Plasma levels of tested parameters were determined by ELISA, CA15–3 by CMIA. Concentrations of all parameters showed statistical significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 26 publications
4
22
1
Order By: Relevance
“…The comparative marker (CA 15-3) showed significantly higher concentrations only in relation to the group of healthy women. Differences between our results and those that were presented in other research papers may be explained by a different composition and selection of study and control groups, as well as a different number of participants [14,16,28].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The comparative marker (CA 15-3) showed significantly higher concentrations only in relation to the group of healthy women. Differences between our results and those that were presented in other research papers may be explained by a different composition and selection of study and control groups, as well as a different number of participants [14,16,28].…”
Section: Discussioncontrasting
confidence: 95%
“…The statistical analysis of the obtained test results revealed that the preoperative plasma concentrations of VEGF and the comparative marker CA 15-3 in patients with BC were significantly higher than the concentrations in the control group of healthy women. Similar results have been obtained in our earlier studies [14][15][16]28] and in the studies by other authors [17,29]. A study by Quaranta et al [30] failed to demonstrate a statistically higher VEGF concentration in comparison to healthy subjects, although only 20 women constituted the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…VEGF levels in patients with breast cancer depend upon different stages of cancer, tumor bulk, local invasion, on cycles of neoadjuvant chemo-radiotherapy received, estrogen receptor status and menopausal state. 27 Baseline serum VEGF levels varied between two groups in our study, though our small study group was homogenous about hormone receptor-positive status, tumor grade and stage (II and III), surgery performed and neoadjuvant chemotherapy received. One of the common causes of increased levels of VEGF measured in serum samples is its release from platelets at the time of venipuncture.…”
Section: Discussionmentioning
confidence: 68%
“…The plasma level of VEGF-B is a sensitive marker in breast cancer [ 34 ]. VEGF signaling involves the binding of the VEGF ligand to receptor tyrosine kinases VEGFR-1, VEGFR-2 and VEGFR-3, resulting in angiogenesis, vasculogenesis and lymphangiogenesis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%